Murder and the SAPS’ policing of illegal firearms in South Africa - Lamb, Guy (Acta criminologica, 2018)
This study sought to determine whether a relationship exists between murder and the policing of illegal firearms by the South African Police Service (SAPS), particularly in high crime areas. The study used a case series approach that examined and retrospectively compared trends in the number of annual cases of murder and illegal possession of firearms and ammunition (IPFA) across 132 high crime police precincts in South Africa for the period from 1994/95 to 2014/15. The data for these two crime categories, which was drawn from the SAPS’ crime database, were then displayed as line charts and thereafter a trajectory pattern analysis was undertaken by means of visual inspection. The trajectory pattern analysis showed that there was an apparent consistent inverse association between the murder and IPFA trajectories in close to 40 per cent of the sample. The article emphasises that an interdisciplinary approach, one that draws from both public health and criminological frameworks, is essential to a more informed understanding of the relationship between firearm controls and firearm murders.